2019
DOI: 10.1021/acs.macromol.9b01643
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur- and Nitrogen-Containing Porous Donor–Acceptor Polymers as Real-Time Optical and Chemical Sensors

Abstract: Real-Time Optical and Chemical Sensors. ChemRxiv. Preprint.Fully aromatic, organic polymers have the advantage of being composed from light, abundant elements, and are hailed as candidates in electronic and optical devices "beyond silicon", yet, applications that make use of their π-conjugated backbone and optical bandgap are lacking outside of heterogeneous catalysis. Herein, we use a series of sulfur-and nitrogen-containing porous polymers (SNPs) as real-time optical and electronic sensors reversibly trigger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
(91 reference statements)
1
25
0
Order By: Relevance
“…This phenomenon can be explained by the narrowing of the polymer bandgap due to molecular backbone protonation, caused by the addition of hydrochloric acid. [ 49a ] In addition, the Stern–Volmer linear relationship, plotted for the different acid concentrations, proves, that HCl interacts with SNP‐MMs and quenches the fluorescence of the excited state of the light‐sensitive material (Figure S18, Supporting Information). [ 51 ]…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This phenomenon can be explained by the narrowing of the polymer bandgap due to molecular backbone protonation, caused by the addition of hydrochloric acid. [ 49a ] In addition, the Stern–Volmer linear relationship, plotted for the different acid concentrations, proves, that HCl interacts with SNP‐MMs and quenches the fluorescence of the excited state of the light‐sensitive material (Figure S18, Supporting Information). [ 51 ]…”
Section: Resultsmentioning
confidence: 97%
“…Previous reports have shown that fully organic SNPs and triazine‐based COF material built from D–A dyads act as rapid and reversible acid‐base chemosensors in the solid state. [ 49 ] Herein we demonstrate the pH response of SNP‐MMs in aqueous media. Upon addition of hydrochloric acid solution at concentrations from 0.1 to 15 wt%, the SNP‐MMs suspension shows an immediate color change (from yellow to red), which can be observed by naked‐eye ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] Moreover,o ur observation agreed well with literature results that the protonation of the imines decreased the optical band gaps in the visible part of the spectrum, thus causing the color change (Figure 3a). [41] Moreover,w e observed that the excess ozone can further react with imine groups after the initial optical color change process (i.e., partial protonation) ( Figure S18). FT-IR spectra ( Figure S19) showed that the C=NH + at the position of 1644 cm À1 was retained, while the characteristic peaks assigned to -NO 2 and -COOH groups gradually appeared.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Moreover, ozone decomposition can be accelerated by initiators such as OH − which can be generated by the protonation of imine groups with water molecules [38–40] . Usually, alteration of the chemical environment of functional groups (e.g., imine) will affect the optical band gaps of materials in the visible part of the spectrum, thus causing the color change [35, 41] . Therefore, imine can be an ideal responsive group for ozone‐related applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation